Factors and Conditions of Reproduction Fixed Funds of Enterprises in the Region - Elvira TAIPOVA; Yuri DOROSHENKO; Sergey GLUKHOV; Irina MAKSAKOVA (Communications of International Proceedings, 2020)
The relevance of the problem under study is due to the fact that fixed assets have an impact on the production activities of the enterprise and, as a result, on the volume of the country's GDP. The state of fixed assets of an enterprise, the quality of its products and, as a result, the profitability of its financial and economic activities, and competitive stability depend on the reproduction of fixed assets. The problem lies in the timeliness and efficiency of reproduction of the company's fixed capital. The solution to the problem depends on the competent implementation of positively influencing factors and preventing the influence of negative factors. The systematization of the factors influencing the process of reproduction of fixed assets makes it possible to build a certain model of reproduction. For this purpose, the concept of reproduction of fixed assets is systematized, the theoretical basis of reproduction is reflected, the foundation of which is the capital of the enterprise. The study grouped the factors of both internal and external environment of the enterprise, which are important in activating the reproduction process of fixed assets. The structures, aspects of activity, which are conductors of certain factors and conditions of the reproductive process, are shown. The practical research site is the branch enterprises of the Ural Federal District, which show the dynamics of fixed assets, their value. The features and contradictions of reproduction of fixed assets of regional enterprises, management of this reproduction are determined. Attention is drawn to the anticipation of the wear and tear of fixed assets in comparison with renovation and modernization, which leads enterprises to competitive weakness. The methodological research tools are statistical data on fixed assets of enterprises from 2013 to 2018. Data for the Ural Federal District are compared with data for the Russian Federation.
Keywords: Fixed assets; reproduction of fixed assets; influencing factors; innovative approach; investment activity.